Quality assessment of mango jam produced by the National Mnago Research and Development Center (NMRDC) - Garceniego, Pearl Hyacinth Cataluña (2006.)
Mango jam produced by the National Mnago Research and Development Center (NMRDC) was assessed by determining the product quality consistency between production batches at one month storage.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Mango; Mango jam; National Mnago Research and Development Center (NMRDC).